2017
DOI: 10.1007/s10803-017-3406-8
|View full text |Cite
|
Sign up to set email alerts
|

Medial Frontal Lobe Neurochemistry in Autism Spectrum Disorder is Marked by Reduced N-Acetylaspartate and Unchanged Gamma-Aminobutyric Acid and Glutamate + Glutamine Levels

Abstract: The nature of neurochemical changes in autism spectrum disorder (ASD) remains controversial. We compared medial prefrontal cortex (mPFC) neurochemistry of twenty high-functioning children and adolescents with ASD without associated comorbidities and fourteen controls. We observed reduced total N-acetylaspartate (tNAA) and total creatine, increased Glx/tNAA but unchanged glutamate + glutamine (Glx) and unchanged absolute or relative gamma-aminobutyric acid (GABA+) in the ASD group. Importantly, both smaller abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 104 publications
7
30
0
Order By: Relevance
“…Specifically, higher SRS‐2 scores (indicative of greater ASD symptomatology) were associated with reduced concentrations of GABA+ in the VIS. This finding is consistent with previous findings linking reductions in GABA to increases in ASD symptoms [Brix et al, ; Carvalho Pereira et al, ]. However, in light of the inverse relationship between VIS GABA+ and VST performance, this result appears to be conflicting, especially given that prior reports have shown that faster, more efficient search is related to ASD symptom severity [Joseph et al, ; Keehn et al, ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically, higher SRS‐2 scores (indicative of greater ASD symptomatology) were associated with reduced concentrations of GABA+ in the VIS. This finding is consistent with previous findings linking reductions in GABA to increases in ASD symptoms [Brix et al, ; Carvalho Pereira et al, ]. However, in light of the inverse relationship between VIS GABA+ and VST performance, this result appears to be conflicting, especially given that prior reports have shown that faster, more efficient search is related to ASD symptom severity [Joseph et al, ; Keehn et al, ].…”
Section: Discussionsupporting
confidence: 89%
“…While GABA+ levels did not differ between groups, results from the present study did show significant differences in other neurochemical concentrations (NAA, tCr, and Glx) between ASD and TD in the rTPJ. In children with ASD, NAA has been found to be lower in various regions of the cortex [Carvalho Pereira et al, 2018;Harada et al, 2011;Kleinhans, Schweinsburg, Cohen, Müller, & Courchesne, 2007;Kubas et al, 2012]. NAA is a neuronal marker representing neurodysfunction or neuronal loss [de Graaf, 2018].…”
Section: Differences In Neurochemical Concentrations In the Rtpjmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroinflammation may explain the dysregulation between GABA and Glutamate cortical neurocircuitry in ASD children, particularly in the frontostriatal system with functional network topology (Cerame et al, 2008 ; Jakab et al, 2013 ; Carvalho Pereira et al, 2017 ; Naaijen et al, 2017 ; Nardone et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…To begin to identify the molecular etiology of aberrant social and repetitive behaviors caused by increased β-cat in our mice, we employed unbiased next-generation sequencing of RNA from the prefrontal cortex (PFC)-a brain region associated with social behavior and implicated in ASD in human studies (Hashemi et al, 2017;Selimbeyoglu et al, 2017;Brumback et al, 2018;Carvalho Pereira et al, 2018;Lazaro et al, 2019). We compared mice with elevated β-cat and altered social and repetitive behaviors (β-cat cOEs, APC cKOs), mice with reduced β-cat that do not display the phenotypes (APC/βcat cKOs) and control littermates.…”
Section: Elevated β-Cat Causes Altered Expression Of Several Genes LImentioning
confidence: 99%